Long non-coding RNA TPT1-AS1 promotes angiogenesis and metastasis of colorectal cancer through TPT1-AS1/NF90/VEGFA signaling pathway - Zhang, Yiyun (Aging (Albany NY), 2020)
LncRNAs have been proven closely correlated to tumor progression. A recent study identified LncRNA TPT1-AS1 (TPT1-AS1) as one of the liver-metastasis associated LncRNAs in colorectal cancer (CRC). In this study, we report that TPT1-AS1 is upregulated in CRC tissues, which is associated with poor prognosis. Functional assays unravel a pro-angiogenesis and metastasis role of TPT1-AS1. Mechanistically, Flexmap 3D assays reveal that TPT1-AS1 upregulates the VEGFA secretion in CRC cells. RNA immunoprecipitation and mRNA stability assays further show that TPT1-AS1 interacts with nuclear factor 90 (NF90) and subsequently promotes the association between NF90 and VEGFA mRNA, which leads to the upregulation of VEGFA mRNA stability. Therefore, we elucidate a new regulatory mechanism of TPT1-AS1 in CRC angiogenesis and targeting the TPT1-AS1/NF90/VEGFA axis may provide a useful strategy for diagnosis and treatment for colorectal cancer patients.